Morphological Characteristics and Body Composition of Elite Volleyball Players: Three Montenegrin Clubs With Most Trophies Participating in European Competitions - Bojanic,Danilo (Sociedad Chilena de Anatomía, 2020)
SUMMARY: The aim of this research was to determine the differences related to morphological characteristics and body composition among volleyball players of the three most successful volleyball clubs in Montenegro. The results of the survey highligted the differences in terms of morphological characteristics and body composition of the players of VC Budva, VC Buduc´nost and VC Jedinstvo. The sample of 43 subjects was divided into three sub-samples, the sub-sample of the subjects consisting of 12 players of VC Budva, the champions of Montenegro 2018-19, the other sub-sample of 17 players of VC Buducnost, the participant in the European CEV Challenge Cup 2018-19, and the one of the examinees including 14 players of VC Jedinstvo, the champions of Montenegro in the season 2017-18. Morphological characteristics in the body composition were evaluated by a battery of 11 variables: body height, body weight, triceps skinfold, biceps skinfold, skinfold of the back, abdominal skinfold, calf skinfold, thigh skinfold, body mass index, fat percentage and muscle mass. The difference between the players of three the most successful volleyball clubs in the morphological characteristics and variables for assessing body composition were determined by ANOVA and LSD Post Hoc test. ANOVA test found statistically significant differences between these three clubs, determined by six variables that estimate the skinfolds, as well as a variable of estimated body mass index (BMI). LSD Post Hoc test found that the volleyball players of VC Budva have significantly lower values ??with regard to triceps skinfold, biceps skinfold, abdominal skinfold, calf skinfold and thigh skinfold, compared to the players of VC Buducnost and VC Jedinstvo, while in the case of variables that evaluates body mass index (BMI), volleyball players of VC Buducnost have less values compared to the players of VC Budva and VC Jedinstvo.